STUDENTS’ PROFICIENCY IN WRITING DESCRIPTIVE AT SENIOR HIGH SCHOOL POPAYATO - Hisasmaria Hisasmaria (Universitas Islam Darul Ulum Lamongan, 2024)
The research objective was to find out the proficiency of the students’ writing descriptive text with vocabulary, mechanics and organization. The population of the research was the first grade students at Senior High School of Popayato in the Academic Year of 2024/2025. The sample was taken by random sampling which consisted of 20 students. This research focused on students' proficiency in writing descriptive paragraph. In collecting the data, researcher used writing test as an instrument. The components analyzed were vocabulary, mechanics and organization. Researcher analyzed students' writing proficiency based on five categories: excellent, good, average, fair, poor. The results of the research showed that students still encounter difficulties in the vocabulary component, mechanics and student organizations.